2016
DOI: 10.1002/jcla.21989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Different Commercial Kits for the Human Papilloma Virus Genotyping

Abstract: The three assays had dissimilar performance of HPV screening capacity and exhibited moderate level of concordance in HPV genotyping. These discrepant results were unavoidable due to difference in type-specific analytical sensitivity and lack of standardization; therefore, we suggested that the efforts to standardization of HPV genotyping kits and adjusting analytical sensitivity would be important for the best clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The test is divided into two sets: set A comprises 14 hrHPV types; and set B comprises 5 possibly carcinogenic/high risk (phr)HPV types and 9 low risk (lr)HPV types. Studies have concluded that Anyplex requires less time [6] and less expertise than most other HPV genotyping assays [7], while still being very sensitive and specific [710].…”
Section: Introductionmentioning
confidence: 99%
“…The test is divided into two sets: set A comprises 14 hrHPV types; and set B comprises 5 possibly carcinogenic/high risk (phr)HPV types and 9 low risk (lr)HPV types. Studies have concluded that Anyplex requires less time [6] and less expertise than most other HPV genotyping assays [7], while still being very sensitive and specific [710].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Lim et al [20], Anyplex TM was compared with MolecuTech REBA HPV-ID and HPV DNAChip and the percentage of HPV genotype agreement ranged from 93.7% to 100.0%. However, relatively high rates of discordance between the three assays were reported for HPV 31, 42, and 44.…”
Section: Discussionmentioning
confidence: 99%
“…However, if multiple HPV types are found in this primary test, a more descriptive test, such as PapilloCheck ® microarray, could be performed. Currently, there is no gold standard for HPV typing ( 39 , 40 ) and the method should be chosen for clinical purpose based on its advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%